Smart Contract Based Data Strategy for Startup Growth in Digital Business Systems - Paroli Paroli; Muhtarom Muhtarom; Mungkap Mangapul Siahaan; Derlina Derlina; Kgomotso Moyo (CORISINTA, 2026)
This study explores how smart contract based data strategies can support startup growth in digital business systems characterized by competition, limited resources, and increasing demand for transparency. In the context of rapid digital transformation, startups require reliable data governance mechanisms to manage transactions, automate business processes, and strengthen stakeholder trust. The background of this research highlights that conventional data management often faces challenges related to data integrity, operational inefficiency, centralized control, and limited transparency, making smart contracts a strategic alternative for supporting secure and automated digital business operations. The objective of this study is to analyze how smart contract based data strategies contribute to startup growth by enhancing data transparency, workflow automation, trust formation, and operational scalability. Employing a qualitative conceptual approach, this study synthesizes academic literature, blockchain related studies, and documented insights on smart contract implementation in digital business environments. The analysis focuses on key dimensions, including decentralized data management, automated transaction execution, transparency mechanisms, security assurance, and workflow efficiency. The results indicate that smart contracts function not merely as blockchain tools but as strategic data mechanisms that enable startups to reduce operational risks, improve process reliability, and strengthen digital business credibility. The conclusion reveals that effective smart contract implementation can support sustainable startup growth by improving data accountability, enhancing stakeholder confidence, and enabling scalable digital operations. This study contributes to blockchain and digital business literature by positioning smart contracts as strategic data capabilities for startup development.